Reduced egg shedding in nematode-resistant ewes and projected epidemiological benefits under climate change. Issue 12 (November 2019) - Rose Vineer, H.; Baber, P.; White, T.; Morgan, E.R.
Graphical abstract: Highlights: Exlana breed ewes were monitored for gastrointestinal nematodes during the peri-parturient period. Ewes selected for resistance when lambs produced fewer eggs as adults. There was no observed reproductive cost to resistance. Simulations predict that lambs of resistant ewes are exposed to reduced infection pressure. Nematode resistance in the female line could help mitigate the impact of climate change on infection pressure. Abstract: Global livestock production is facing serious new challenges, including climate-driven changes in parasite epidemiology, and anthelmintic resistance, driving a need for non-chemotherapeutic methods of parasite control. Selecting for genetic resistance to gastrointestinal nematode infection could reduce reliance on chemical intervention and mitigate increases in parasite challenge due to climate change. Ewes of the composite Exlana breed with a range of estimated breeding values (EBVs) based on nematode faecal egg counts (FECs) were monitored during the peri-parturient period on two farms in southwestern England. Ewes with low EBVs ("resistant") had lower FECs during the peri-parturient period than those with high EBVs ("susceptible"): the mean FEC was reduced by 23% and 34% on Farms 1 and 2, respectively, while the peak FEC was reduced by 30% and 37%, respectively. Neither EBV nor FEC were correlated with key performance indicators (estimated milk yield, measured indirectly using 8 week lamb weight, and ewe weight loss during lactation). Simulations predict that the reduced FECs of resistant ewes would result in a comparable reduction in infection pressure (arising from eggs shed by ewes) for their lambs. Furthermore, although the reduced FECs observed were modest, simulations predicted that selecting for nematode resistance in ewes could largely offset predicted future climate-driven increases in pasture infectivity arising from eggs contributed by these ewes. Selective breeding of the maternal line for nematode resistance therefore has potential epidemiological benefits by reducing pasture infectivity early in the grazing season and alleviating the need for anthelmintic treatment of ewes during the peri-parturient period, thus reducing selection pressure for anthelmintic resistance. These benefits are magnified under predicted future climate change. The maternal line warrants more attention in selective breeding programmes for nematode resistance.